1995
DOI: 10.1111/j.1471-0528.1995.tb11425.x
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre comparative study of 17 experts and an intelligent computer system for managing labour using the cardiotocogram

Abstract: Objectives To investigate 1. whether an intelligent computer system could obtain a performance in labour management comparable with experts when using cardiotocograms (CTGs), patient information, and fetal blood sampling and 2. whether experts could be consistent and agree in their management of labour. Subjects An intelligent computer system and 17 clinicians experienced in fetal monitoring from 16 centres in the UK. Design Fifty cases with complete intrapartum CTGs and clinical data were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(78 citation statements)
references
References 25 publications
5
66
0
4
Order By: Relevance
“…An average of 21% of the CTG traces were assessed different at the second observation, and only 22% of the traces were equally assessed by all of the four obstetricians at both observations. In another study 4 , intra-observer agreement varied from moderate to good (n (kappa) ¼ 0.43 to 0.77). In eight studies assessing ante-and intrapartum CTG traces 4 -11 , inter-observer agreement varied from poor to very good (n ¼ 0.11 to 1.00).…”
Section: Introductionmentioning
confidence: 95%
“…An average of 21% of the CTG traces were assessed different at the second observation, and only 22% of the traces were equally assessed by all of the four obstetricians at both observations. In another study 4 , intra-observer agreement varied from moderate to good (n (kappa) ¼ 0.43 to 0.77). In eight studies assessing ante-and intrapartum CTG traces 4 -11 , inter-observer agreement varied from poor to very good (n ¼ 0.11 to 1.00).…”
Section: Introductionmentioning
confidence: 95%
“…Studies on inter-and intra-observer variability have shown that the introduction of computer-assisted classifications of CTG readings has resulted in a more reliable categorization of CTG patterns overall [37,46]. The benefit of "online" CTG analysis is that asssessment can be done almost in realtime.…”
Section: Electronic Online Assessmentmentioning
confidence: 99%
“…In 1995, a similar comparison was made of 50 intrapartum cases evaluated by 17 experts from 16 different centres [26] . The system agreed with experts in the management of 67.3 % of cases, for a κ value of 0.31.…”
Section: Guardian Tm and Infant ® (K2 Medical Systems Tm Plymouth Uk)mentioning
confidence: 99%